Dinamika Servicescape dan Kualitas Pelayanan Terhadap Kepuasan Wajib Pajak: Penelitian - Diovany Tirtana; Bambang Guritno; Anis Turmudhi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Servicescape Dynamics and Service Quality on Taxpayer Satisfaction is the subject of this study. This type of research is quantitative. The focus of this study is Taxpayer which payed taxes at Samsat Kota Semarang II period 11 until 16 August 2025 (6 workday) and the sample of this study consisted of 267 people who responded, according to the Slovin formula with Margin of Error 5 %. This study used a simple random sampling method and questionaire with Likert Scale 1-10. The research findings is that servicescape has a significant positive influence on Taxpayer satisfaction and service quality has a significant positive influence on Taxpayer satisfaction. This means that the Quality of Service must be built to be able to increase satisfaction for Taxpayers because it will create a sense of pleasure, and a good Servicescape felt by Taxpayers will be able to increase Taxpayer Satisfaction because they feel a comfortable environment.